The Vision Book of Football Records 2013 - Batty, Clive (Surrey Vision Sports Pub., 2012)
The fourth edition of this popular annual football records book,The Vision Book of Football Records 2013, is crammed with records, facts, stats and amazing feats from the world's greatest game, making it the perfect Christmas present for football fans of all ages
Include Color Illustration
Keywords: Soccer